2010
DOI: 10.1016/j.virol.2010.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of an antibody binding energy hot spot on domain III of the dengue 2 envelope glycoprotein exploited for neutralization escape

Abstract: Previous crystallographic studies have identified a total of 11 DENV-2 envelope protein domain III (ED3) residues (K305, F306, K307, V308, V309, K310, I312, Q325, P364, K388, and N390) that interacted, through both side- and main-chain contacts, with the Fab of a dengue virus (DENV) subcomplex-specific neutralizing monoclonal antibody (MAb) 1A1D-2 (Lok et al., 2008). Here, we used DENV-2 recombinant ED3 mutants of the MAb 1A1D-2 structural epitope residues to determine the functional epitope of this MAb. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 39 publications
6
43
0
Order By: Relevance
“…These residues could be further investigated by mutation to understand how mutation giving an impact on the binding affinity either enhance or harm the binding activity. Three residues of the binding sites as reported by Lok [14] were further studied by Gromowski [7]. Mutation of these three residues harmed the binding of antibody and domain III.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These residues could be further investigated by mutation to understand how mutation giving an impact on the binding affinity either enhance or harm the binding activity. Three residues of the binding sites as reported by Lok [14] were further studied by Gromowski [7]. Mutation of these three residues harmed the binding of antibody and domain III.…”
Section: Resultsmentioning
confidence: 98%
“…There is an immunoglobulin-like fold which is a common structure as cell receptor and it was observed to project further away from both domains I and domain II [7]. Domain III was found that respond to the antibody neutralisation as well [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This approach was used successfully with a recombinant ED3 and effectively removed the amino acid side chains, while retaining the native ED3 conformation (Gromowski et al, 2010). The WT and three mutant ICs (K305A, K310A and P384A) were transcribed in vitro and electroporated into Vero cells (African green monkey kidney).…”
mentioning
confidence: 99%
“…Mouse monoclonal antibodies (MAbs) that neutralize DENV map to all three domains (35). However, the monoclonal antibodies with the strongest neutralization are serotype specific and map to EDIII (37)(38)(39)(40)(41)(42), which is a region of Ïł100 amino acids that folds into an immunoglobulin-like domain and has been implicated in host receptor binding (43). The minor surface glycoprotein, prM/M, plays a role in proper folding of E and particle assembly and is present as uncleaved prM in the immature particle and partly or fully cleaved M in the mature particle (44).…”
mentioning
confidence: 99%